Targeting effector pathways in RAC1P29S-driven malignant melanoma. (4th July 2021) - Uribe-Alvarez, Cristina; Guerrero-Rodríguez, Sandra Lucía; Rhodes, Jennifer; Cannon, Alexa; Chernoff, Jonathan; Araiza-Olivera, Daniela
ABSTRACT: Malignant melanoma is characterized by mutations in a number of driver genes, most notably BRAF and NRAS . Recent genomic analyses revealed that 4-9% of sun-exposed melanomas bear activating mutations in RAC1, which encodes a small GTPase that is known to play key roles in cell proliferation, survival, and migration. The RAC1 protein activates several effector pathways, including Group A p21-activated kinases (PAKs), phosphoinositol-3-kinases (PI3Ks), in particular the beta isoform, and the serum-response factor/myocardin-related transcription factor (SRF/MRTF). Having previously shown that inhibition of Group A PAKs impedes oncogenic signalling from RAC1 P29S, we here extend this analysis to examine the roles of PI3Ks and SRF/MRTF in melanocytes and/or in a zebrafish model. We demonstrate that a selective Group A PAK inhibitor (Frax-1036), a pan-PI3K (BKM120), and two PI3Kβ inhibitors (TGX221, GSK2636771) impede the growth of melanoma cells driven by mutant RAC1 but not by mutant BRAF, while other PI3K selective inhibitors, including PI3Kα, δ and γ, are less effective. Using these compounds as well as an SRF/MRTF inhibitor (CCG-203, 971), we observed similar results in vivo, using embryonic zebrafish development as a readout. These results suggest that targeting Group A PAKs, PI3Kβ, and/or SRF/MRTF represent a promising approach to suppress RAC1 signalling in malignant melanoma.